Sustained release of medications in liquid form: utility, advantages, and disadvantages - Alsalhy, Saja; Masheta, Dhafir (Pharmakeftiki, 2025)
Dosage forms function as vehicles for delivering drugs into the body, with oral formulations typically classified as solid, liquid, or gaseous. Among these, liquid oral dosage forms are often preferred due to their superior bioavailability relatively to solids ones, as well as their enhanced absorption and ease of administration. These formulations are prepared by dissolving or suspending active pharmaceutical ingredients in suitable solvents. Key challenges in liquid formulations – such as taste masking, dose uniformity, and excipient optimization (e.g. sweeteners and viscosity modifiers) – are critical for ensuring patient acceptability and effective drug delivery. Modified-release dosage forms (including controlled-release, extended-release, delayed-release, and sustained-release systems) are designed to improve therapeutic outcomes by enabling prolonged drug delivery, reducing dosing frequency, and minimizing side effects. Sustained-release drug delivery systems are particularly beneficial in chronic conditions such as hypertension, where continuous medication is required. These systems aim at maintaining consistent plasma drug concentrations while attenuating peak levels to reduce the risk of toxicity. The ideal sustained-release formulation would support a single-dose regimen that delivers therapeutic effects over days, weeks, or longer. Several systems (such as diffusion-, dissolution-, and osmotic pressure-controlled systems) have been developed in order to achieve sustained release. However, challenges remain, including incomplete drug release, the risk of dose dumping, and the need to maintain therapeutic drug concentrations in a consistent manner.